Digitization of the financial sector of Azerbaijan - Z. F. Mamedov (Informaciâ i Innovacii)
Purpose. To develop the theoretical, methodological and methodological foundations for organizing banking activities in Azerbaijan based on financial innovations in the digital economy. In Azerbaijan, digital technologies are largely seen as an important strategic vector in the national policy for economic diversification.The theoretical basis of the article consists of the works of foreign and domestic specialists, substantiating scientific and theoretical directions and concepts, principles of formation and development of banking activities in the context of the introduction of financial innovations, key definitions of economic theory in relation to the activities of banks in the digital economy. The study used methods of systemic, structural, functional and comparative analysis of economic reality, objective assessments and determination of vectors for the development of the functional framework to study the consequences of the introduction of financial innovations by Azerbaijani credit institutions.